CuO/Cu based superhydrophobic and self-cleaning surfaces. (June 2016) - He, Zhiwei; Zhang, Zhiliang; He, Jianying
Abstract: CuO/Cu based superhydrophobic surfaces with ordered micro/nanostructures have been prepared via a solution-immersion process combining with photolithography and argon ion beam etching. CuO nanoneedles grow only inside microholes on copper substrate due to delaying effect of both residual photoresist and carbon layer produced during Ar etching. The hierarchical structures and surfaces show a water contact angle of 152⁰, a contact angle hysteresis of 3⁰, and a low water adhesion force of 15 μN, indicating a good superhydrophobicity. The obtained surfaces also keep itself clean from carbon black, chalk dust and water, enabling a great potential in self-cleaning and anti-fouling applications. Graphical abstract: